A LOW COST IOT-BASED SMART ENERGY MONITORING AND LOAD MANAGEMENT SYSTEM FOR RESIDENTIAL AND SMALL SCALE APPLICATIONS: A CASE STUDY AT ABDULLAHI FODIO UNIVERSITY OF SCIENCE AND TECHNOLOGY, ALIERO - Usman, Abubakar Sadik; Abubakar, Nasiru; Adua, Abba Muhammad; Jarere, Umar Mohammad (FUDMA JOURNAL OF SCIENCES, 2025)
Electricity supply in Nigeria is characterized by instability, inefficiency, and high costs of imported smart meters, limiting their widespread adoption. This study presents the design and implementation of a locally adaptable, low-cost smart energy monitoring and load management system for residential and small-scale industrial applications. The system integrates an Arduino-based IoT platform with voltage and current sensors, relay modules, and cloud-based visualization to enable real-time monitoring and intelligent load control. The prototype was calibrated against standard meters and deployed across three households with diverse load profiles over a 30day period. Key results showed an average reduction in energy consumption of 12%, with measurement accuracy of ±2.1% for voltage and ±1.8% for current. The system successfully automated load prioritization during peak demand, minimized unnecessary consumption, and improved user awareness through a mobile dashboard. Comparative analysis indicates that the achieved energy savings are competitive with international benchmarks (10 to15%) while maintaining significantly lower cost through local hardware sourcing. User feedback confirmed ease of use, though challenges included Wi-Fi instability and occasional resets after power surges. The findings demonstrate that affordable IoT-based systems can strengthen energy efficiency, reduce costs, and support Nigeria’s progress toward Sustainable Development Goal 7 (affordable and clean energy). Future improvements will focus on solar PV integration, GSM-based communication for offline regions, and scalability across larger residential and industrial clusters.